2021
DOI: 10.1007/s42452-021-04624-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of out-of-plane mechanical properties of carbon fiber reinforced epoxy resin composite by incorporating the multi-walled carbon nanotubes

Abstract: In this study, epoxy hybrid nanocomposites reinforced by carbon fibers (CFs) were fabricated by a filament winding. To improve out-of-plane (transverse) mechanical properties, 0.5 and 1.0 Wt.% multi-walled carbon nanotubes (MWCNTs) were embedded into epoxy/CF composites. The MWCNTs were well dispersed into the epoxy resin without using any additives. The transverse mechanical properties of epoxy/MWCNT/CF hybrid nanocomposites were evaluated by the tensile test in the vertical direction to the CFs (90º tensile)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The MWCNT reinforced epoxy molds were prepared (see Figure 2) to study the effect of adding the nano reinforcement where the hardener and carbon nanotube mixture, was manually stirred for 10 min to form a homogeneous suspension by using a simple low shear mixing technique since repairing pipeline requires simple and quick preparation steps in practice and avoiding nanocomposite preparation methods such as using sonication with additives (where this method need additional steps to remove the additives, lowering the molecular weight of the polymer which lead to softening problem and reagglomeration problem in the time of removal procedure (Mirsalehi et al, 2021)), followed by adding the epoxy resin to the mixture. Then the composite mixture was added from one corner into the mold-to avoid bubble formation-and left to be cured at room temperature for 7 days (Fadhil et al, 2016).…”
Section: Materials and Testingmentioning
confidence: 99%
“…The MWCNT reinforced epoxy molds were prepared (see Figure 2) to study the effect of adding the nano reinforcement where the hardener and carbon nanotube mixture, was manually stirred for 10 min to form a homogeneous suspension by using a simple low shear mixing technique since repairing pipeline requires simple and quick preparation steps in practice and avoiding nanocomposite preparation methods such as using sonication with additives (where this method need additional steps to remove the additives, lowering the molecular weight of the polymer which lead to softening problem and reagglomeration problem in the time of removal procedure (Mirsalehi et al, 2021)), followed by adding the epoxy resin to the mixture. Then the composite mixture was added from one corner into the mold-to avoid bubble formation-and left to be cured at room temperature for 7 days (Fadhil et al, 2016).…”
Section: Materials and Testingmentioning
confidence: 99%
“…2-4 the most appropriate fibres would be carbon or basalt, while the most appropriate matrices are epoxy or bio-based epoxy resin. It has been reported that small amount of carbon nanotubes (CNT), i.e., 0.5-1wt%, can increase the strength of carbon/epoxy composites by 7-16% without changing the modulus [38][39][40]. Based on this DMM, three composites were chosen for study, including carbon/epoxy (C/E), basalt/bio-epoxy (B/BE) and carbon/CNT/epoxy (C/CNT/E).…”
Section: Definition Of Scopementioning
confidence: 99%
“…Carbon fiber reinforced composites (CFRC) are known for their high specific strength and modulus in longitudinal direction, which is not the case in through-the-thickness direction. 1 To improve that performance of CFRC, carbon based nanofillers such as single-wall carbon nanotubes (SWCNT), multi-wall carbon nanotubes (MWCNT), and carbon black are incorporated. 2 The presence of such nanofiller in composite structures provides resistance to mechanical loads and growth of cracks through physical interlocking in polymer matrices, 3 including the thickness direction.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The optimum content of MWCNT in epoxy composites and the corresponding improvement in flexural strength and modulus are dependent on the dispersion method. Some of the works in the literature mention, respectively, 32% and 98% increase with ultrasonic dispersion of MWCNT (0.25 wt%), 11 18.0% and 11.6% for high energy sonication of MWCNT (0.3 wt%), 12 45% and 17% for mechanical mixing of MWCNT/carbon nanofibers (0.3 wt%), 13 25% and 11% for mechanical mixing of MWCNT (2.4 wt%), 14,15 15.4% and 7.15% for ultrasonic/ high shearing of MWCNT (1 wt%), 1 15.6% and 10.2% for mechanical mixing/sonication with amine-functionalized MWCNT (0.5 wt%), 16 and 28% and 19% for sonication with carboxyl-functionalized MWCNT (1.5 wt%). 17 Recently, ionic liquids (IL) have emerged in the modification of carbon-based nanofillers as well as in the preparation of epoxy resins with improved properties.…”
Section: Introductionmentioning
confidence: 99%